1991
DOI: 10.1164/ajrccm/144.3_pt_1.668
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health and PM10Pollution: A Daily Time Series Analysis

Abstract: This study evaluated changes in respiratory health associated with daily changes in fine particulate pollution (PM10). Participants included a relatively healthy school-based sample of fourth and fifth grade elementary students, and a sample of patients with asthma 8 to 72 yr of age. Elevated PM10 pollution levels of 150 micrograms/m3 were associated with an approximately 3 to 6% decline in lung function as measured by peak expiratory flow (PEF). Current day and daily lagged associations between PM10 levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
239
0
14

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(271 citation statements)
references
References 8 publications
10
239
0
14
Order By: Relevance
“…*Published emission factors but not reported in text. **Emission factors reported explicitly in text ᴬ Age groups according to health outcomes; ᴯ Such as ≥18 years or ≥30 years; C Environmental Benefits Mapping and Analysis Program using the concentration response function from chronic bronchitis [63], acute bronchitis [64], all-cause mortality [65,104], COPD hospitalization (Moolgavgkar 2000a, 2003) [66], asthma emergency room visits [67], work loss days [68], asthma (symptoms) [69], minor-restricted activity days [70], acute MI [71], respiratory disease [72], lower respiratory symptoms [73], and cough among asthmatic children [74]; D Probable, but not specified explicitly in the text; ᴱ Health And Air Pollution Study in New Zealand to estimate the morbidity and mortality health costs associated with traffic emissions [82]; F CVD admission >64 years: [75]; ᴳ Mortality: <75 and >75 years, respiratory disease (65 years) [76], and lung cancer [104] Morbidity: CVD, respiratory disease [76], and lung cancer [104]; H Method of transport emission estimation is quite vague in determination of emission factors; I External cost of energy to estimate the automotive pollution impact on health in Europe [81]; J Cerebrovascular disease and lower respiratory tract infection [77], preterm weight [78], low term weight [79], and CVD (Mustafic 2012) [80]; K Value of a Life Year: calculation of monetary benefits of mortality reduction using a life tables approach. …”
Section: Resultsmentioning
confidence: 99%
“…*Published emission factors but not reported in text. **Emission factors reported explicitly in text ᴬ Age groups according to health outcomes; ᴯ Such as ≥18 years or ≥30 years; C Environmental Benefits Mapping and Analysis Program using the concentration response function from chronic bronchitis [63], acute bronchitis [64], all-cause mortality [65,104], COPD hospitalization (Moolgavgkar 2000a, 2003) [66], asthma emergency room visits [67], work loss days [68], asthma (symptoms) [69], minor-restricted activity days [70], acute MI [71], respiratory disease [72], lower respiratory symptoms [73], and cough among asthmatic children [74]; D Probable, but not specified explicitly in the text; ᴱ Health And Air Pollution Study in New Zealand to estimate the morbidity and mortality health costs associated with traffic emissions [82]; F CVD admission >64 years: [75]; ᴳ Mortality: <75 and >75 years, respiratory disease (65 years) [76], and lung cancer [104] Morbidity: CVD, respiratory disease [76], and lung cancer [104]; H Method of transport emission estimation is quite vague in determination of emission factors; I External cost of energy to estimate the automotive pollution impact on health in Europe [81]; J Cerebrovascular disease and lower respiratory tract infection [77], preterm weight [78], low term weight [79], and CVD (Mustafic 2012) [80]; K Value of a Life Year: calculation of monetary benefits of mortality reduction using a life tables approach. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, confidence intervals for the urban and nonurban areas overlapped widely. If the observed difference is interpreted as a true difference between the urban and nonurban areas, it might be explained by the higher asthma medication use in the nonurban symptomatic panels, as it has been suggested that medication use attenuates the association between air pollution and respiratory health [13,40]. Bronchodilator use was not associated with particle concentrations and the health outcomes for which particle effects were observed in the urban panels (morning PEF and URS) are probably least affected by asthma medication use.…”
Section: Discussionmentioning
confidence: 97%
“…The few studies that have been performed in adults have mainly investigated asthma patients [8±11]; one study focused on a random sample of the general population [12]. Previous panel studies in children have demonstrated acute effects of air pollution in, among others, children with mild chronic respiratory symptoms [5,13,14]. It is not clear whether adults with mild chronic respiratory symptoms are also susceptible to acute effects of air pollution such as transient changes in lung function and respiratory symptoms.…”
mentioning
confidence: 99%
“…Individual daily PEF readings were transformed into a daily population variable representing the population mean for each day of the individual deviations from the child-specific mean PEF [12,17,18]. This was done separately for morning and evening PEF (DPEFam and DPEFpm).…”
Section: Methodsmentioning
confidence: 99%